2022
DOI: 10.1111/1475-6773.13958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating implementation strategies to support documentation of veterans' care preferences

Abstract: Objective: To evaluate the effectiveness of feedback reports and feedback reports + external facilitation on completion of life-sustaining treatment (LST) note the template and durable medical orders. This quality improvement program supported the national roll-out of the Veterans Health Administration (VA) LST Decisions Initiative (LSTDI), which aims to ensure that seriously-ill veterans have care goals and LST decisions elicited and documented. Data Sources: Primary data from national databases for VA nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…For this reason, we chose to continue our work with HBPC and to capitalize on our experiences and existing partnership with the national HBPC program office. In contrast to the wide range of LST template completion in HBPC programs at the end of the LTC QUERI, mean LST template completion rates across all VA CLCs exceeded 80% [31]. This high baseline completion rate limited the potential impact of additional implementation efforts, and thus, we turned our attention to the VA CNH program, where LST template completion ranges from 2 to 87% (Internal VA data, 2022).…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, we chose to continue our work with HBPC and to capitalize on our experiences and existing partnership with the national HBPC program office. In contrast to the wide range of LST template completion in HBPC programs at the end of the LTC QUERI, mean LST template completion rates across all VA CLCs exceeded 80% [31]. This high baseline completion rate limited the potential impact of additional implementation efforts, and thus, we turned our attention to the VA CNH program, where LST template completion ranges from 2 to 87% (Internal VA data, 2022).…”
Section: Overviewmentioning
confidence: 99%
“…The team used lessons learned from the LTC QUERI to inform PERSIVED. For example, LTC QUERI outcomes demonstrated that more intensive engagement with champions and implementation facilitation yielded better outcomes [31]. We also recognized that LST template completion rates for Veterans in VA HBPC varied greatly across programs [32] following the initial implementation of the LSTDI, which indicated significant opportunities for improvement.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In late 2020, the Preferences Elicited and Respected for Seriously Ill Veterans through Enhanced Decision-Making (PERSIVED) VA Quality Enhancement Research Initiative or QUERI, quality improvement program was developed to address high variation in completion of life-sustaining treatment templates for seriously ill Veterans. The PERSIVED QUERI was established following the completion of the VA Long-Term Care QUERI program (3,6,7). The Long-Term Care QUERI supported implementation of the LSTDI in VA's longterm care settings, which included VA nursing homes, known as Community Living Centers, and VA Home Based Primary Care (HBPC) programs (2).…”
Section: Introductionmentioning
confidence: 99%